Low-Level Laser therapy improves vision in a patient with retinitis pigmentosa - Ivandic, Boris; Ivandić, Tomislav (Photomedicine and laser surgery, 2014)
Objective: This case report describes the effects of low-level laser therapy (LLLT) in a single patient with retinitis pigmentosa (RP). Background data: RP is a heritable disorder of the retina, which eventually leads to blindness. No therapy is currently available. Methods: LLLT was applied using a continuous wave laser diode (780 nm, 10 mW average output at 292 Hz, 50% pulse modulation). The complete retina of eyes was irradiated through the conjunctiva for 40 sec (0.4 J, 0.333 W/cm2) two times per week for 2 weeks (1.6 J). A 55-year-old male patient with advanced RP was treated and followed for 7 years. Results: The patient had complained of nyctalopia and decreasing vision. At first presentation, best visual acuity was 20/50 in each eye. Visual fields were reduced to a central residual of 5 degrees. Tritan-dyschromatopsy was found. Retinal potential was absent in electroretinography. Biomicroscopy showed optic nerve atrophy, and narrow retinal vessels with a typical pattern of retinal pigmentation. After four initial treatments of LLLT, visual acuity increased to 20/20 in each eye. Visual fields normalized except for a mid-peripheral absolute concentric scotoma. Five years after discontinuation of LLLT, a relapse was observed. LLLT was repeated (another four treatments) and restored the initial success. During the next 2 years, 17 additional treatments were performed on an “as needed” basis, to maintain the result. Conclusions: LLLT was shown to improve and maintain vision in a patient with RP, and may thereby have contributed to slowing down blindness.
Gesehen am 16.09.2020